Hak Atas Tanah Dan Bangunan Berdasarkan Pelepasan Hak (Studi Kasus Putusan MA Nomor 2523 K/Pdt/2015) - Gabriella Patricia Trinita Tomasoa; Merry Tjoanda; Jenny Kristiana Matuankotta (Faculty of Law, Universitas Pattimura, 2021)
Introduction: In obtaining land rights, it can be obtained through transfer of rights as regulated in the Agrarian Law (UUPA). One of the ways to transfer of rights is by transferred rights, which means that the transfer of the right of ownership from the owner to another party is due to a legal act. However, in committing a legal act, the party who transfers the property rights is carried out on the basis of bad faith, in which the first party turns out to be committing a legal act on the land object which is not the right of ownership of the first party to the second party and also to the third party over the same land object that cause a dispute because of the act against the law made by the first party.Purposes of the Research: The purpose of this paper is to determine the procedure for acquiring rights to land and buildings based on the relinquishment of rights and legality of ownership of land based on the relinquishment of rights.Methods of the Research: The research method used is normative research with analytical descriptive type through a conceptual approach, a statutory approach, and case studies. The method of collecting legal materials used is library research.Results of the Research: Based on the results of the research: first, the procedure for obtaining rights to land and buildings, the rights are transferred or released due to a legal act. Acquisition of rights is carried out based on applicable legal procedures or provisions. Second, in transferring rights, only entitled persons can take legal actions to avoid cause of disputes and losses of other parties.